Modeling of the induced expression for high-level production of a foreign protein by recombinant E. coli under the control of the T7 phage promoter - (:unkn) unknown (Elsevier BV, 2003)
A structured four-compartment mathematical model is proposed for describing the behaviour of three expression systems. In system [R], Tag I endonuclease gene was expressed under the control of T7 RNA polymerase promoter in recombinant Escherichia coli cells. Methylase protection was provided either by cloning the Taq I methylase gene on to a second plasmid (system [R, M]) or by constructing a recombinant plasmid harbouring both genes (system [R + M]). Considering the promoter strength, the inducer effect is included in the rate equation for foreign protein production. A separate set of parameters was estimated for simulations of the uninduced and induced phases (dual-parameter set) of systems [R] and [R, M]. A single parameter set describing both phases was also determined. Simulation results indicate that the dual-parameter approach is more successful in predicting the experimental observations. Model validation conducted on system [R + M] using parameter sets of system [R, M] revealed good agreement. © 2003 Elsevier Science Ltd. All rights reserved.
Keywords: Compartment; Escherichia coli; Induced expression; Structured modeling; T7 phage promoter; Taq I